Study guides

☆☆

Q: How do you solve x plus 3y equals 2?

Write your answer...

Submit

Still have questions?

Related questions

x = 5, y = -1

10 - (3y + 2) = 2 First solve the bracket: 10 - 3y + 2 = 2 Bring all constants to one side: 10 + 2 - 2 = 3y Simplify: 10 = 3y y = 31/3 (3.33333333333)

7y = 3y - 12 4y = -12 y = -3

To solve for 2 unknown variables you need 2 independent equations. You have only 1.

x + y = -2 2x + 3y = -9 You solve this by elimination - multiply both sides of first equation by 3, then subtract, solve for x, then substitute in any of the equations to solve for y 3x + 3y = -6 2x + 3y = -9 subtracting, x = 3 substituting into 1st equation, y = -2-3 = -5

Multiply first equation by 1.5, giving 3x + 3y = 12, but we are told that 3x + 3y = 6. If there isn't an error in the question then 2 = 1!

5y-2y= 3y+2 5y-2y-3y= 2 0y= 2

(3y + 5)(y - 2)

2x-3y=13

(2, 2)

2 - (y + 2) = 3y Remove brackets: 2 - y - 2 = 3y Combine like terms: 0 = 4y Divide both sides by 4: 0 = y

n=3,y=4 2(n+3y)=30

y=8

If: y-2+3y =10 Then: y+3y = 10+2 And: 4y = 12 Divide both sides by 4 to find the value of y: y = 3

y=2

y = -1

2x + 3y = 12 x = 1.45, so 2 * 1.45 + 3y = 12 2.9 + 3y = 12 3y = 12 - 2.9 = 9.1 y = 9.1/3 = 3.0333... or 91/30 or 3 1/30.

2x + 3y = 11Subract 2x from each side:3y = 11 - 2xDivide both sides by 3:y = 11/3 - (2/3)x

(2,3)

(-1, 0)

12y + 2 or 2*(6y+ 1)

6x+7y=-6 3(-2x-3y=2) +________ -2y=0 => y=0 Therefore x=-1

y + 2y = 4 (2+1)y = 4 3y = 4 (3y)/3 = 4/3 y = 4/3 = 1.3333333333333333333

y = 8.6

y=-2/3x